Effect of Photoaging on the Structure, Optical Properties and Roughness of One-Shade Composite Restoratives - Aikaterini Petropoulou; Maria Dimitriadi; Spiros Zinelis; Maria Antoniadou; George Eliades (Journal of Functional Biomaterials)
The aim of the study was to evaluate changes in the degree of C=C conversion (DC%), chemical structure, optical properties and roughness of one-shade composites before/after photoaging. Τhe one-shade materials tested were Charisma Topaz One (CHT), Clearfil Majesty ES-2 Universal (MES), Essentia Universal (ESU) and Omnichroma (OMN), with G-aenial Anterior (CNA) serving as control. Specimens (2 mm thickness) were prepared and tested for DC% and chemical structure (ATR–FTIR spectroscopy), optical properties (L*a*b*–ΔΕ, translucency parameter–TP, opalescence parameter–OP, contrast ratio–CR and total transmittance–TT by UV–Vis spectroscopy) and roughness (Sa, Sz, Sdr, Sds and Sc by optical profilometry) before and after photoaging (Xe-arc weatherometer). Significant differences were found in DC% between top–bottom surfaces (ESU, OMN before; ESU, CNA after). Photoaging improved DC%, reduced ester peaks implying photodegradation, reduced L* (CHT, OMN, CNA), a* (CHT, CNA), b* (OMN, CNA), TP (all, except for MES), OP (only MES), CR (only MES, but an increase in CNA) and TT (CHT, OMN). OMN, CNA and MES demonstrated ΔΕ > 3.3. Photoaging significantly increased all roughness parameters in all materials, except for MES (Sz, Sdr, Sc) and OMN (Sdr). Although listed in the same group, significant differences were found in one-shade composites before and after photoaging. Several products were strongly affected by photoaging, demonstrating evidence of photodegradation, an increased roughness and color changes exceeding the clinically acceptable levels.